The Impact of Financing Structure on Common Stock Prices - Hussain Hadi Abdulameer (Technium Business and Management, 2024)
The pricing of common stock is significantly influenced by the financing structure. The cost required for businesses to secure outside funding in order to support their operations and projects is referred to as their financing structure. This expense could include interest on debt and investor returns on capital contributed to the business. A high cost of financing structure will raise the cost of capital and lower the value of common stock. The interest expenses incurred on debt mean that the cost of the financing structure will have an impact on the profits of the company. The required return will rise in the event that financing costs are high, which will lower the valuation of the company and possibly lower the price of common stock. Through its effects on the cost of capital, the profits of the company and valuation, and the demand for stocks, the cost of financing structure has a direct and indirect impact on the price of common stocks. It should be mentioned that other elements, such as political and economic ones, business performance, and rivalry in the market, also have an impact on the price of common stock.